THEORETICAL BASIS OF BUILDING AN EDUCATIONAL SOCIETY IN THE NEW UZBEKISTAN - Sh.M. Ismatov (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
What do we mean by optimizing the socio-economic and spiritual-ethical foundations of building an enlightened state in new Uzbekistan, what should we pay attention to, what creative ideas will give us strength, unlimited knowledge, guaranteed knowledge for our youth We understand such phenomena as the right to education and a decent and healthy lifestyle in the future, as well as the provision of rights to every citizen based on the rule of law. In this regard, our updated Constitution, adopted recently, first of all, according to the above main ideological content, expresses that New Uzbekistan, which is being built in our country, is an enlightened state, and all efforts in our country are aimed at this. Representatives of different classes of people in the world and in our country often discuss the question of what kind of society we live in, whether we are moving towards a secular state or a religious society. Our main values are love, peace and kindness. In recent years, the importance of education, medicine, and various spheres of social life, especially the values of the holy religion of Islam, increases the urgency of this question. Therefore, in this article, we want to think about the essence of the new state and enlightened society, which is being built in the new Uzbek language